Zinc supplementation for respiratory illness and acute gastroenteritis as complement treatment for covid-19 - Atif Amin, Baig; Chandrika, Murugaiah; Constance, Liew Sat Lin (2020)
An outbreak of atypical pneumonia by the novel coronavirus disease 2019 (COVID-19), has been reported in Wuhan, China since December, 2019. It is a severe respiratory illness with many other symptoms such as gastroenteritis. Clinical trials has proved that Zn is a promising supplement that can ease of cough, fever and vomiting, dysentery, respiratory illness, diarrhea duration and recovery, duration of hospitalization and morbidity. This article suggests a potential role, which should be considered in the clinical management, and safeness for Zn supplementation for respiratory illness and acute gastroenteritis as compliment treatment for covid-19.